2017
DOI: 10.1016/j.mmcr.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Chromoblastomycosis caused by Rhinocladiella similis: Case report

Abstract: We report a case of chromoblastomycosis in lesions on the chest and foot. Itraconazole was chosen as the initial treatment for this patient, who was followed up for 8 months before becoming noncompliant. The pathogenic fungal species was identified as Rhinocladiella similis by ITS region sequencing. In vitro analyses indicate that the fungus was sensitive to posaconazole and itraconazole. This report presents R. similis as a new agent of chromoblastomycosis and raises the hypothesis that this species could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 13 publications
3
21
1
1
Order By: Relevance
“…Only a few, mostly imported, skin infections have been reported in Europe, none of which were due to R. similis . CBM by R. similis was described and isolated for the first time in 2003 from the foot of a Caucasian man living in Brazil, and a second case was identified in 2017 in the skin lesion of a Mexican rural worker . To our knowledge, our case represents the first case of CBM by RS in Europe and the third published case worldwide.…”
mentioning
confidence: 71%
“…Only a few, mostly imported, skin infections have been reported in Europe, none of which were due to R. similis . CBM by R. similis was described and isolated for the first time in 2003 from the foot of a Caucasian man living in Brazil, and a second case was identified in 2017 in the skin lesion of a Mexican rural worker . To our knowledge, our case represents the first case of CBM by RS in Europe and the third published case worldwide.…”
mentioning
confidence: 71%
“…The etiological agents of CBM belong to the order Chaetothyriales, family Herpotrichiellaceae , and include: Fonsecaea pedrosoi, Fonsecaea monophora, Cladophialophora carrionii, Fonsecaea nubica, Phialophora verrucosa, Fonsecaea pugnacius, Rhinocladiella aquaspersa, Cladophialophora samoensis, Cyphellophora ludoviensis, Rhinocladiella tropicalis, and Rhinocladiella similis. 1 , 5 , 11 , 12 , 18 - 25 Studies on the ribosomal DNA (rDNA) internal transcribed spacer showed that Fonsecaea pedrosoi and Fonsecaea compacta are identical species. 26 …”
Section: Etiologymentioning
confidence: 99%
“…However, they both cause harm to humans if not handled safely. R. similis can cause chromoblastomycosis, which is a tropical and subtropical skin disease caused by accidental inoculation through the environment [11]. Likewise, the type strain of T. irritans was isolated from moldy paint and found to cause skin irritation upon exposure [5].…”
Section: Discussionmentioning
confidence: 99%